Upaya Cina menjadi Kekuatan Maritim dalam Indian Ocean Rim Association (IORA) - Qodarsasi, Umi; Rachmawati, Tety (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
After the economic reform in 1978, China experienced a rapid economic growth. The open door policy adopted on economic reforms succeeded in attracting many foreign investors in the sector of manufacture. Along with its status as a new power of the world economy, China is also ambitious to become the largest maritime power. The Indian Ocean is a strategic area to strengthen China's steps to support economic needs and become a maritime power. To achieve strategic interests in the Indian Ocean Region, China joins as an IORA partner. China’s effort to dominate at the IORA is not only to recruiting rival countries, but also to built strategic partnerships with the countries in the Indian Ocean region. Besides Pakistan and Myanmar, China has also established strategic partnerships with Iran, Bangladesh and Sri Lanka. For strategic partner, China is seen as an alliance in strengthening politics in their country and is a supplier of military weapons and technology with affordable prices. This paper will explain the China's interests in the IORA and China's position compared to other IORA member, and also China's strategy. The results obtained shows that China has the potential to become a maritime power at the IORA.